2010
DOI: 10.1039/b926662c
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic zinc buffering and muffling: Their role in intracellular zinc homeostasis

Abstract: Our knowledge of the molecular mechanisms of intracellular homeostatic control of zinc ions is now firmly grounded on experimental findings gleaned from the study of zinc proteomes and metallomes, zinc transporters, and insights from the use of computational approaches. A cell's repertoire of zinc homeostatic molecules includes cytosolic zinc-binding proteins, transporters localized to cytoplasmic and organellar membranes, and sensors of cytoplasmic free zinc ions. Under steady state conditions, a primary func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
393
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(401 citation statements)
references
References 142 publications
7
393
0
1
Order By: Relevance
“…Although the extracellular bioavailable zinc levels are yet to be precisely determined, indications are that these will also be in the nanomolar to picomolar range, similar to intracellular bioavailable zinc levels. Thus bioavailable zinc levels in plasma are in a range of 20 -210 pM (64). In plasma, the total zinc level remains steady at 14.7 M even after a daily diet supplement with 80 mg zinc in the AREDS trials (38).…”
Section: Discussionmentioning
confidence: 99%
“…Although the extracellular bioavailable zinc levels are yet to be precisely determined, indications are that these will also be in the nanomolar to picomolar range, similar to intracellular bioavailable zinc levels. Thus bioavailable zinc levels in plasma are in a range of 20 -210 pM (64). In plasma, the total zinc level remains steady at 14.7 M even after a daily diet supplement with 80 mg zinc in the AREDS trials (38).…”
Section: Discussionmentioning
confidence: 99%
“…As metal concentrations in the heat-stable cytosol largely increased between days4 and16, there was no further increase in MTLP levels. Colvin and colleagues (Colvin et al, 2010) suggested that, with Zn at least, MT might be involved in buffering and muffling reactions that are caused by the Zn 2+ binding to MT with differing affinities. From this, we could postulate that, at day4, MTLPs had been induced following exposure, but the MTLPs were not saturated.…”
Section: Discussionmentioning
confidence: 99%
“…-10 210 M (Colvin et al, 2010;Yu et al, 2014). We therefore concluded that p53-R175H is nonfunctional in the cell because it is unable to bind Zn 21 under physiologic conditions.…”
mentioning
confidence: 93%